Fitness Cost of Transgenic cry1Ab/c Rice Under Saline-Alkaline Soil Condition - Fu, Jianmei; Song, Xiaoling; Liu, Biao; Shi, Yu; Shen, Wenjing; Fang, Zhixiang; Zhang, Li (Frontiers in Plant Science, 2018)
The environmental release and biosafety of transgenic Bt crops have attracted global attention. China has a large area of saline-alkali land, ideal for conducting a large-scale application and production of Bt transgenic rice. Therefore an understanding of the fitness of Bt transgenic rices in saline-alkaline soils and the ability to predict its long-term environmental impact are important for the future sustainable use of these crops. In the present study, transgenic cry1Ab/c rice Huahui1, for which a national biosafety certificate was obtained, was grown on simulated normal farmland and saline-alkaline soils without target insect pressure. The expression pattern of exogenous Cry1Ab/c protein, vegetative and reproductive fitness were assessed; the expression of the exogenous Cry1Ab/c protein in the transgenic rice grown on saline-alkaline soil was lower than it was for the same strain grown on farmland soil. In both soil conditions, vegetative growth as evaluated by tiller number and biomass, and reproductive growth as measured by filled grain number and grain yield per plant all showed a significant fitness cost for Huahui1 compared with the parental rice Minghui63 grown in the same soil conditions. The fitness cost was also moderately higher in saline-alkaline soil for Huahui1 than for Minghui63. Therefore, the ecological risk of cry1Ab/c transgenic rice is not expected to be higher than that for parental rice Minghui63 if the former should happen to escape into natural saline-alkaline soil. The results of this study will provide a scientific basis for improving the assessments of the environmental safety assessment of the insect-resistant transgenic rice strain Huahui1 before it is commercialized.